Borosilicate Activation of (Difluoroiodo)toluene in the gem‐Difluorination of Phenyldiazoacetate Derivatives. Issue 27 (26th July 2016) - Sinclair, Geoffrey S.; Tran, Richard; Tao, Jason; Hopkins, W. Scott; Murphy, Graham K.
Abstract : A combined experimental and computational investigation was conducted to identify a mild and effective Lewis‐acidic activator for TolIF2 in the gem ‐difluorination of diazo compounds. Computationally, borosilicate, a common constituent of laboratory glassware, was found to spontaneously activate TolIF2, and an extensive experimental survey confirmed borosilicate as the most effective activator to date. The key to realizing this borosilicate‐activated reaction was the use of high purity TolIF2, which is prepared by a reproducible, multigram‐scale synthesis. Abstract : A computational and experimental search for mild Lewis‐acidic activators for (difluoroiodo)toluene (TolIF2 ) has identified borosilicate glass as the most effective activator (to date) in the gem ‐difluorination of phenyl diazoacetate derivatives.